2022
DOI: 10.3390/v14040729
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Treatment Integrase Inhibitor Resistance and Natural Polymorphisms among HIV-1 Subtype C Infected Patients in Ethiopia

Abstract: Dolutegravir-based antiretroviral therapy (ART) has been scaled up in many developing countries, including Ethiopia. However, subtype-dependent polymorphic differences might influence the occurrence of HIV-drug-resistance mutations (HIVDRMs). We analyzed the prevalence of pre-treatment integrase strand transfer inhibitor (INSTI) HIVDRMs and naturally occurring polymorphisms (NOPs) of the integrase gene, using plasma samples collected as part of the national HIVDR survey in Ethiopia in 2017. We included a total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 78 publications
1
15
0
Order By: Relevance
“…The Sanger method does not detect drug-resistance minority variants below 20% of the virus population. The most frequently reported major INI RAMs include codons T66A/I/K, E92G/Q, F121Y, Y143C/H/R/S, S147G, Q148H/R/K, N155H, and R263K [ 1 , 13 , 26 ], while accessory RAMs and other mutations have been largely reported in recent studies from SSA [ 21 , 22 , 23 , 24 , 25 , 27 ]. The prevalence of both major and accessory mutations in the ART-naïve population is very low (0.5%) and likely results from cases of transmitted INI resistance and the cumulative natural occurrence of mutations without selective drug pressure [ 4 , 26 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Sanger method does not detect drug-resistance minority variants below 20% of the virus population. The most frequently reported major INI RAMs include codons T66A/I/K, E92G/Q, F121Y, Y143C/H/R/S, S147G, Q148H/R/K, N155H, and R263K [ 1 , 13 , 26 ], while accessory RAMs and other mutations have been largely reported in recent studies from SSA [ 21 , 22 , 23 , 24 , 25 , 27 ]. The prevalence of both major and accessory mutations in the ART-naïve population is very low (0.5%) and likely results from cases of transmitted INI resistance and the cumulative natural occurrence of mutations without selective drug pressure [ 4 , 26 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nine accessory INI-resistance mutations were found in this study, among which L74I/M, T97A, and E157Q, were identified most frequently. These mutations were observed in Cameroon and Ethiopia [ 24 , 27 ], and L74M/I and M50I have been reported in the untreated population. Although many reports have shown that accessory INI-resistance mutations (including naturally occurring polymorphisms) do not compromise the effectiveness of INI-based regimens [ 29 , 30 ], other studies have revealed that several mutations can act synergistically or additively to decrease drug susceptibility [ 31 , 32 ]; for instance, the combination of L74M and G163R associated with T79A, has been reported by Abram et al as further reducing susceptibility to RAL and/or EVG in the absence of primary INI-resistance mutations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We defined two HIV drug resistance outcomes: the level of resistance to DTG and the presence of known drug resistance mutations (DRMs). The Stanford HIV Database version 9•0 and the Stanford HIVdb algorithm 27 were used to categorise drug resistance levels as susceptible (score below 10), potential low (10)(11)(12)(13)(14), low (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29), intermediate or high (>60). The same approach was used to assess resistance to all other antiretroviral drugs, whereby drug resistance to tenofovir alafenamide (not covered by the Stanford algorithm) was considered equal to tenofovir resistance.…”
Section: Hiv Drug Resistancementioning
confidence: 99%
“…INSTI polymorphisms that may decrease susceptibility to INSTIs are not infrequent; 3 for instance, mutations like G163R/K are polymorphic in subtype F viruses but can also be non-polymorphic when considering other HIV-1 subtypes; 4 however, if alone, they have little impact on INSTI activity. 5–7 …”
mentioning
confidence: 99%